PVAc/PEDOT:PSS/graphene-iron oxide nanocomposite (GINC): an efficient thermoelectric material - Dey, Abhijit; Maity, Arunava; Khan, Md Abdul Shafeeuulla; Sikder, Arun Kanti; Chattopadhyay, Santanu (RSC Advances, 2016)
A green method for the synthesis of a graphene-iron oxide nanocomposite (GINC) and its PVAc based polymer nanocomposites was reported in an earlier communication. The fabricated PVAc-GINC film exhibited a conductivity of 2.18 x 104 S m(-1) with a Seebeck coefficient of 38.8 mu V K-1. Hence, the power factor (PF) reached a value of 32.90 mu W m(-1) K-2 which is 27 fold higher than a thermoelectric material based on a PVAc-graphene composite as reported in the contemporary literature. In continuation of the above mentioned study, PEDOT:PSS was used to further enhance the power factor (PT) and figure of merit (ZT) of the system. During evaluation, a PEDOT: PSS/GINC composite (5 : 95) showed a remarkable increase in various thermoelectric properties like electrical conductivity (8.0 x 10(4) S m(-1)) with a Seebeck coefficient of 25.42 mu V K-1 and thermal conductivity 0.90 m(-1) K-1. Hence PF and ZT reach up to 51.93 mW m(-1) K-2 and 0.017, respectively. To improve the mechanical strength of the polymer composite, cellulose fibre was also employed. By the addition of cellulose fibre, though the mechanical strength of the composite increases the PF reaches 5.6, which is 10 times lower than the PEDOT:PSS/GINC composite.